The Use of Video-Based Learning Media Assisted By LMS Moodle to Improve Student Learning Outcomes in Social Research Materials - Omika, Hefri Asra (Universitas Tanjungpura, 2024)
The low learning outcomes of students are a problem that occurs in sociology learning. The literature review shows that using video media integrated with Moodle LMS can help overcome these problems. The research aims to determine whether using video-based learning media integrated with the Moodle LMS on social research material can improve sociology learning outcomes. This research is a classroom action research with 2 cycles. The subjects of this study were students in class E - 1 at SMAN Titian Teras H. Abdurrahman Sayoeti, with a total of 28 students. This study found that there was an increase in student learning outcomes in sociology learning using video-based learning media that was integrated with the Moodle LMS. This is evidenced by the average student learning outcomes in cycle 1, which is 80. Meanwhile, the average student learning outcomes in cycle 2, namely 91. Meanwhile, a comparison between pretest and posttest shows that there is an increase in student learning outcomes based on competency achievement indicators.